The Effects of Acupressure on Improving Health and Reducing Cost for Patients Undergoing Thoracoscopic Surgery - Hsu, Hsing-Chi; Tseng, Kai-Yu; Fang, Hsin-Yuan; Huang, Tzu-Min; Kuo, Chi-Chung; Chen, Li-Li; Ma, Wei-Fen (International journal of environmental research and public health, 2022)
Objectives. This study aimed to assess the effectiveness of practicing acupressure on the Shenmen and Neiguan acupoints with a view to reduce anxiety and improve the comfort and physical health of patients undergoing thoracoscopic surgery. Methods. A total of 100 hospitalized patients undergoing thoracoscopic surgery were assigned randomly into the experimental (n = 49) and control groups (n = 51). Subjects in the experimental group received routine care plus acupressure on the Shenmen and Neiguan acupoints, while those in the control group received regular routine care. The data were collected using demographic information, physical and surgical data, the Visual Analog Scale (VAS)-A, the State-Trait Anxiety Inventory Y Form (STAI-Y1), and Shortened General Comfort Questionnaire scores. The linear mixed model was used to examine the influences of acupressure on VAS-A and STAI-Y1 scores at different time points before and after the surgery to observe group-by-time interactions. Results. The mean age of the subjects was 60.97 years. All subjects had mild-to-moderate anxiety after surgery and showed a statistically significant decline in regression coefficients on the first and second days after the intervention (β = −11.61, p = 0.002; β = −18.71, p < 0.001). Similarly, for STAI-YI scores, the data showed a significant difference in the pre-test and post-test interactions between the two groups (β = 4.72, p = 0.031). Conversely, acupressure did not have a statistically significant difference on comfort (F = 2.953, p = 0.057). Compared with the control subjects, the experimental subjects used less morphine and developed side effects less frequently (p < 0.01). They were also able to get out of bed after surgery 163.79 min earlier (p < 0.05). Conclusions. Acupressure is a simple and easy-to-practice treatment. Acupressure on the Shenmen and Neiguan acupoints reduces anxiety and improves recovery in patients after undergoing thoracoscopic surgery.